Sperm Morphology of Post-wash Sample and Its Association with Clinical Pregnancy among the Couples Undergoing Intrauterine Insemination: A Cohort Study - Syamala Prathyusha; NS Kubera; Srimathi Murugesan; Jitendar Kumar Sharma; Sujatha Venkatraman; Anusuya Ram (Journal of Human Reproductive Sciences)
Background: Intrauterine insemination (IUI) is an effective and inexpensive method of managing patients with unexplained and male factor infertility. It is attempted before proceeding to more invasive assisted reproductive techniques such as in vitro fertilisation and intracytoplasmic sperm injection. Numerous semen parameters have been assessed to indicate successful outcomes with IUI. It is debatable to what extent morphological parameters influence the IUI success. Aim: We aimed to study the association of sperm morphology and other semen parameters in post-wash inseminated samples with clinical pregnancy rate (CPR) among the couples undergoing IUI. Settings and Design: This was a prospective cohort study conducted between March 2022 and January 2024 in the Department of Obstetrics and Gynaecology, Women and Children’s Hospital, Jawaharlal Institute of Postgraduate Medical Education and Research, Puducherry. Materials and Methods: A total of 127 couples presenting with infertility (underwent 246 IUI cycles) were included after written informed consent from study participants, semen collection was done and pre-wash and post-wash semen were analysed as per the World Health Organization Sixth Edition Laboratory Manual for sperm morphology. Statistical Analysis Used: Demographic data, semen analysis parameters and CPR results were compared and analysed using SPSS version 19.0. Results: Among 246 IUI cycles, post-wash sperm morphology was normal in 47.6% and teratozoospermia was noted in 52.4%. Clinical pregnancy was reported in 10.6% (n = 26) of couples, of which 6.1% (n = 15) had post-wash normal sperm morphology and 4.5% (n = 11) had post-wash teratozoospermia. When categorised by strict morphology ≤1%, 2%–3%, 4%–5% and ≥5%, the CPR was 0.0%, 12.0%, 12.6% and 12.9%, respectively. Even though clinical pregnancy was noted only with >1% sperm morphology, there was no significant association between sperm morphology and CPR. Conclusion: No significant differences in CPR were noted following IUI in couples with post-wash normal and abnormal sperm morphology. Hence, the current study findings suggest that sperm morphology should not be a criterion to exclude couples from undergoing IUI.